English Word Stress Production of Male and Female Madurese Students - Syarifah, Syarifah; Warsono, Warsono; Wuli Fitriati, Sri (Universitas Negeri Semarang, 2020)
Pronunciation is very important in speaking. Most of English learners usually face some difficulties in pronouncing English words properly especially in word stress. One of the influential factors is because of first language interference. Therefore, the objective of this study was to analyze students’ stress production of two, three, four, five, and six syllable words in order to explain the possible factors that influence the Madurese male and female students in pronouncing English word and to analyze students’ stress production of syllable words in order to explain the influence of gender on students’ pronunciation. This research employed qualitative descriptive research. The subjects of this study were 20 students of Madura Islamic University. The data were collected by using questionnaires, students’ recording and table. The result of this study shows that Madurese dialect gives significant positive influence on two syllable words stress on first syllable. It is because in Madurese dialect sound system, stress in two syllable words are frequently produced on first position. Meanwhile, male and female students were almost the same in pronouncing stress correctly on three until four syllable words. On the contrary, they put stress improperly on words that consist of five to six syllables. In this case, the students put the stress correctly and incorrectly from three until six syllable words, it does not indicate that it was influenced by Madurese local language. The possible factors affecting the students’ word stress is because of motivation, age, target language exposure, lack of pronunciation training and lack of knowledge about the rules of word stress. Last, Gender does not influence much in pronunciation moreover in word stress. In segmental feature, female students’ pronunciation consonant is better than that of male students but not in vowel. The students who pronounce correctly were the students who always train themselves. Pedagogically, this study can be the additional information to develop male and female students’ stress production.